ANALISIS HUKUM PELAKSANAAN PERATURAN PEMERINTAH NOMOR 78 TAHUN 2010 TENTANG REKLAMASI DAN PASCATAMBANG TERHADAP KEWAJIBAN REKLAMASI LAHAN DI PT. MULTI HARAPAN UTAMA (MHU) KABUPATEN KUTAI KARTANEGARA - Maylinda Nur Laila (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractIndonesia is a country that has a lot of Mining Company Permits, that in carrying out mining exploitation activities that should not be forgotten are reclamation and post-mining activities. Reclamation and post-mining activities are regulated in Indonesia, namely Government Regulation Number 78 Year 2010. Despite the post-mining regulations, until now the handling of ex-mining land still leaves many dug pits that cause environmental damage to cause casualties. That based on the matters as described above, the writer is interesting to conduct research on the reclamation implementation activities carried out by PT. Multi Harapan Utama (MHU), as one of the executors of coal mining activities in Kutai Kartanegara Regency, East Kalimantan Province. In this writing, the author uses empirical juridical methods with the data used include primary data obtained directly from the research location and secondary data obtained from legal materials owned by the author. Data collection is done by observation and interview techniques and analyzed in such a way as a descriptive analytical description. The author's research results can be concluded that PT. Multi Harapan Utama (MHU) has or is conducting post-mining land reclamation in accordance with applicable laws and regulations in order to achieve environmental standards even though there are some obstacles in the technical implementation of post-mining land reclamation work.